Facile fabrication of three-dimensional nanofibrous foams of cellulose@g-C3N4@Cu2O with superior visible-light photocatalytic performance. (1st March 2023) - Xue, Xiaolin; Zhang, Jian; Li, Mei; Ao, Chenghong; Wang, Qunhao; Zhao, Jiangqi; Zhang, Wei; Lu, Canhui
Abstract: In this work, a unique three-dimensional nanofibrous foam of cellulose@g-C3 N4 @Cu2 O was prepared via electrospinning followed by a foaming process. A cellulose solution in DMAc/LiCl containing g-C3 N4 and CuSO4 was applied for electrospinning, while aqueous alkali was used as the coagulation bath. The solidification of electrospun cellulose/g-C3 N4 nanofibers would be accompanied with in-situ formation of Cu(OH)2 nanoparticles. Interestingly, the hydrogen gas (H2 ) generated from NaBH4 could transform the two-dimensional membrane into a three-dimensional foam, leading to the increased specific surface area and porosity of the material. Meanwhile, the Cu(OH)2 nanoparticles attached on the electrospun nanofibers were reduced to Cu2 O to form a p-n heterostructure between Cu2 O and g-C3 N4 . The as-prepared cellulose@g-C3 N4 @Cu2 O foam exhibited a high degradation efficiency (99.5 %) for the dye of Congo Red under visible light radiation. And ·O 2− was discovered to be the dominant reactive species responsive for dye degradation. Moreover, the cellulose@g-C3 N4 @Cu2 O could maintain its initial degradation efficiency even after seven cycles of reuse, suggesting the excellent stability and cycling performance. Graphical abstract: Unlabelled Image